The origins of theatre in Zimbabwe - Matiza, Vimbai M. (UNISA Centre for Latin American studies, 2016)
The word theatre is a controversial term which has stimulated debate among scholars owing to the fact that theatre can be referred to as a form of art and entertainment and on the other hand as theatrical performances in other activities. This paper is aimed at exploring the historical origins of theatre in Zimbabwe and further seeks to make a distinction between performance and theatre. It therefore, follows that the paper is quite significant in enlightening the recipients about the two dimensions of the same coin. In addition, the paper will have the liberty to examine some historical performances which have culminated into theatre in contemporary Zimbabwe. The latter is derived from the notion that performance is an inclusive term whilst theatre is only a connection that reaches from the ritualisations of humans through performances in everyday life. Zimbabwe has a history of theatre which emanates from its tradition. The history of theatre in Zimbabwe can he traced back to numerous ceremonies, religious rituals and community festivals that define the existence of the people, which justifies to the entire population the fact that 'theatre' was in existence since time immemorial through different activities as will be explored in the paper. In exploring the concept' the paper will use the theory of orature which looks at the art of talking as the origins of theatre in Zimbabwe and Africa at large.